Morphological, Liquid Crystal and Optical Band Energy Properties of Polyphosphates - Akram, Evon; El-Hiti, Gamal A; Ahmed, Dina S; Rashad, Alaa Adnan; Al Dahhan, Wedad H; Yousif, Emad (Al-Nahrain Journal of Science, 2019)
New metallic liquid crystalline polyphosphates showed thermotropic nematic liquid crystal phases (2.13–2.24 eV). The surface morphology of polyphosphates was examined by the scanning electron microscope and showed rough surface and micro pore structure which an indication of the presence of several crystalline domains.